Repurposing the anti-epileptic drug sodium valproate as an adjuvant treatment for diffuse intrinsic pontine glioma. - Clare L Killick-Cole; William G B Singleton; Alison S Bienemann; Daniel J Asby; Marcella J Wyatt; Lisa J Boulter; Neil U Barua; Steven S Gill (PLoS ONE)
Targeting epigenetic changes in diffuse intrinsic pontine glioma (DIPG) may provide a novel treatment option for patients. This report demonstrates that sodium valproate, a histone deacetylase inhibitor (HDACi), can increase the cytotoxicity of carboplatin in an additive and synergistic manner in DIPG cells in vitro. Sodium valproate causes a dose-dependent decrease in DIPG cell viability in three independent ex vivo cell lines. Furthermore, sodium valproate caused an increase in acetylation of histone H3. Changes in cell viability were consistent with an induction of apoptosis in DIPG cells in vitro, determined by flow cytometric analysis of Annexin V staining and assessment of apoptotic markers by western blotting. Subsequently, immunofluorescent staining of neuronal and glial markers was used to determine toxicity in normal rat hippocampal cells. Pre-treatment of cells with sodium valproate enhanced the cytotoxic effects of carboplatin, in three DIPG cell lines tested. These results demonstrate that sodium valproate causes increased histone H3 acetylation indicative of HDAC inhibition, which is inversely correlated with a reduction in cell viability. Cell viability is reduced through an induction of apoptosis in DIPG cells. Sodium valproate potentiates carboplatin cytotoxicity and prompts further work to define the mechanism responsible for the synergy between these two drugs and determine in vivo efficacy. These findings support the use of sodium valproate as an adjuvant treatment for DIPG.